Indocyanine green fluorescence imaging-assisted laparoscopy resection of retroperitoneal tumors in children: case report and literature review - Luo, Yuanyuan; Zhang, Hong; Wu, Qiang; Chen, Yan; Ye, Zhihua; Liu, Ruiyu; Chai, Chengwei (Frontiers in Pediatrics, 2024)
This study examined the applicability of indocyanine green (ICG) fluorescence imaging to assist the laparoscopic resection of retroperitoneal tumors in pediatric patients via an abdominal approach. Conducted prospectively at the Guangzhou Women and Children’s Medical Center from May to September 2023, the research included three pediatric cases, for whom laparoscopic retroperitoneal tumor resections were performed utilizing ICG fluorescence imaging. In each case, ICG was intravenously administered (0.3 mg/kg) prior to surgery, enabling the visualization of vital vascular structures through real-time fluorescence imaging. The trocar’s placement was guided by a “four-hole” technique from the healthy side in a 70-degree lateral decubitus position. The operations were accomplished successfully without any complications. Pathological analysis of the patients identified one case of Wilms tumor of the embryonal type, one ganglioneuroblastoma of the mature type without N-MYC gene amplification, and one mature cystic teratoma. The findings suggest that with careful patient selection and skilled surgical execution, the utilization of ICG fluorescence imaging in the laparoscopic resection of retroperitoneal tumors is both safe and effective in children. This approach significantly improves the visualization of critical blood vessels, thus enhancing surgical safety.